Business model validation : Practical assessment of an early-stage digital business model - Lütt, Magnus; Lukeš, Martin, 1976-; Pakzad, Hassieb; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The thesis analyzes the validation of early-stage digital business models. In the first part, frameworks for business model development and their approach to validation are outlined. In the second part, the validation of a business model is carried out and examined in practice. Frameworks are applied, and attempts are examined to achieve validation through various measures. An MVP and its development are described, along with the measurement of user behavior and collection of customer feedback. Ultimately, the results are evaluated, and practical guidance for digital entrepreneurs is derived.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses